Newborns Referred for Therapeutic Hypothermia: Association between Initial Degree of Encephalopathy and Severity of Brain Injury (What About the Newborns with Mild Encephalopathy on Admission?) - Gagne-Loranger, Maude; Sheppard, Megan; Ali, Nabeel; Saint-Martin, Christine; Wintermark, Pia (American Journal of Perinatology, 2016)
Objective The aim of this article was to describe the severity of brain injury and/or mortality in a cohort of newborns referred for therapeutic hypothermia, in relation to the degree of encephalopathy on admission, and to especially look at the ones with initial mild encephalopathy.Study Design Term newborns with perinatal depression referred to our neonatal intensive care unit for possible hypothermia treatment from 2008 to 2012 were enrolled prospectively. The modified Sarnat score on admission was correlated with severity of brain injury on brain imaging and/or autopsy.Results A total of 215 newborns were referred for possible cooling. Sixty percent (128/215) were cooled. Most of the not-cooled newborns with an available brain magnetic resonance imaging (85% = 50/59) had an initial mild encephalopathy, and 40% (20/50) developed brain injury. Some cooled newborns had an initial mild encephalopathy (12% = 13/108); only 31% (4/13) developed brain injury.Conclusion Our results demonstrated that several newborns with an initial mild encephalopathy developed subsequent brain injury, especially when they were not cooled.
Keywords: asphyxiated newborns; neonatal encephalopathy; magnetic resonance imaging; brain injury